Combinatorial Efficacy of Human Mesenchymal Stem Cell Secretome and Ursodeoxycholic Acid in Ameliorating Renal Dysfunction: A Synergistic Approach in a Rat Model of Cholestatic Injury - Mariani Devi; Parish Budiono; Gana Adyaksa (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Cholestatic nephropathy, historically termed cholemic nephropathy, represents a critical intersection of hepatic and renal pathology where the systemic retention of nephrotoxic cholephiles induces severe acute kidney injury. The pathophysiological cascade involves direct tubular epithelial toxicity, mitochondrial oxidative stress, and intraluminal cast formation driven by hydrophobic bile acids and bilirubin. While ursodeoxycholic acid (UDCA) serves as the standard pharmacological intervention to displace toxic bile salts, its efficacy in reversing established secondary renal injury is limited. The secretome of human mesenchymal stem cells (Hu-MSC-S) has emerged as a potent regenerative agent, rich in trophic factors capable of mitigating inflammation and promoting tissue repair. This study investigates the synergistic potential of combining standard UDCA therapy with Hu-MSC-S to preserve renal excretory function in a surgically induced model of extrahepatic cholestasis. Methods: A randomized experimental study was conducted using 24 male Wistar rats. Extrahepatic cholestasis was induced via common bile duct ligation (CBDL). Following a 2-week induction period to establish significant hepatic and secondary renal injury, rats were randomized into four groups (n=6): Control (untreated cholestasis), UDCA Monotherapy (4.5 mg/200g body weight orally), Hu-MSC-S Monotherapy (0.2 ml/kg intraperitoneally), and combination therapy (UDCA + Hu-MSC-S). Treatments were administered weekly for four weeks. Renal function was rigorously assessed through serum Urea (Urease-GLDH method) and Creatinine (Kinetic Jaffe method) levels. Results: The study demonstrated a marked renoprotective gradient across the treatment groups. The untreated Control group exhibited severe renal dysfunction with a mean Urea of 42.60 mg/dL and Creatinine of 3.18 mg/dL. Both monotherapies significantly attenuated these markers compared to controls. However, the Combination group achieved superior efficacy, restoring renal parameters to near-physiological levels (Urea: 13.08 mg/dL; Creatinine: 1.32 mg/dL). Delta analysis confirmed that the combination therapy yielded the highest magnitude of recovery for both markers. Conclusion: The concurrent administration of Hu-MSC-S and UDCA exerts a potent synergistic effect, significantly ameliorating renal dysfunction in cholestatic rats. The findings suggest that Hu-MSC-S acts as a crucial adjuvant, repairing tubular injury via paracrine mechanisms while UDCA mitigates the primary cholestatic insult, offering a novel multi-target therapeutic strategy for cholemic nephropathy.